2018
DOI: 10.3390/polym10030313
|View full text |Cite
|
Sign up to set email alerts
|

Strength of PLA Components Fabricated with Fused Deposition Technology Using a Desktop 3D Printer as a Function of Geometrical Parameters of the Process

Abstract: Abstract:The current paper studies the influence of geometrical parameters of the fused deposition modeling (FDM)-fused filament fabrication (FFF) 3D printing process on printed part strength for open source desktop 3D printers and the most popular material used for that purpose-i.e., polylactic acid (PLA). The study was conducted using a set of different nozzles (0.4, 0.6, and 0.8 mm) and a range of layer heights from the minimum to maximum physical limits of the machine. To assess print strength, a novel ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
183
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 236 publications
(203 citation statements)
references
References 10 publications
18
183
1
1
Order By: Relevance
“…This can be done by adjusting the printing temperature as in the present case. It can be also achieved by using a smaller layer height as shown by Kuznetsov et al, Mostafa et al, Zhang et al, Popescu et al and many others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done by adjusting the printing temperature as in the present case. It can be also achieved by using a smaller layer height as shown by Kuznetsov et al, Mostafa et al, Zhang et al, Popescu et al and many others.…”
Section: Resultsmentioning
confidence: 99%
“…This can be done by adjusting the printing temperature as in the present case. It can be also achieved by using a smaller layer height as shown by Kuznetsov et al, [23] Mostafa et al, [24] Zhang et al, [25] Popescu et al [2] and many others. With regard to the elongation at break, there is a substantial reduction of this quantity (up to 89%) compared to the elongation at break of ASA wire.…”
Section: Mechanical Performancementioning
confidence: 99%
“…Kuznetsov et al 2018 [37] showed that an increase in the nozzle diameter not only reduces printing time, but also increases sample strength. Nozzle diameter has a significant influence on interlayer cohesion.…”
Section: Fig 5 Image Of Nozzle Diameter [33]mentioning
confidence: 99%
“…That is because the best results of the ultimate tensile stress, yield stress and elasticity modulus were observed for a raster angle of 0º/90º [35]. In the most of studies investigating the effect of different parameters on the strength of FDM technologies the mechanical properties are tested on flat samples oriented horizontally during the printing process [37]. Letcher and Waytashek [55] showed that the mechanical properties such as the ultimate tensile strength can be improved by exchanging the raster angle of specimens made of PLA Fig.10 Raster angles [54] According to Montero et al's [56] results of study, strength values of producing of material with various raster angles via fused deposition modeling and injection molded material is given in Fig.11 and Fig.12.…”
Section: Raster Anglementioning
confidence: 99%
See 1 more Smart Citation